Integration strategies for the success of mergers and acquisitions in financial services companies - Barros, Rafael Hernandez; Domínguez, Ignacio López (Journal of Business Economics and Management, 2013)
The research shows how managers can plan a successful integration process following a merger and acquisition. Presents a series of frameworks which discuss understanding value creation in mergers and acquisitions, selecting the right strategy and managing the integration process; drawn largely from research studies and interviews made to managers with experience in leading integration processes of financial services companies in Europe, Latin America and USA. Concludes that, by following the key drivers framework described, managers can turn the integration process into a successful project, and academics can focus their post-merger research having into account the opinion of managers.